Reengineering Rear Projection? A Genealogy of Virtual Production Spaces and their Aesthetic and Logistical Potential - O'Meara, Jennifer (Routledge, 2025)
This chapter situates emergent uses of virtual production spaces within film history to argue that the challenges and opportunities offered by virtual production technologies are less radical when positioned within the much longer history of screen compositing technologies and pre-recorded sets. The analysis identifies overlaps between rear projection and virtual production in terms of their logistical benefits; approaches to lighting, cinematography, colour and scale; emphasis on careful pre-planning and requirements in terms of training and personnel. I also identify parallels in the form of global challenges (World War 2 and the COVID-19 pandemic) serving as catalysts for the adoption of both screen technologies. My approach draws on archival trade sources focused on background plates and composite images, which are compared with contemporary accounts of virtual production in trade journals. Overall, I demonstrate how greater attention to the technological precursors to virtual production can offer important lessons for those using it or considering using it. In particular, industry scepticism related to virtual production might be somewhat alleviated through increased contemporary awareness of precisely how and why esteemed filmmakers, including Alfred Hitchcock, Stanley Kubrick and Joseph L. Mankiewicz, deployed virtual production’s precursors to successful creative effect.
The Screens of Virtual Production: What's Real?
PUBLISHED
Keywords: Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Genes & Society; Identities in Transformation